Building Learning Organization in Malaysian Organizations Context - Ahmad, Abdul Rahman (Management Research Journal, 2013)
There is no simple way to build a learning organization. Each organization must develop a structure and style that is best suited for its own people, history, skill base, technology, mission and culture. Besides that, there is a need for leader’s image in building a learning organization. The objective of this paper is to highlight the study of the building of a learning organization that has been conducted in selected Malaysian organizations. Three organizations were selected for this study. The nature of the organizations are varies based on their own functions. Organization A is a service oriented, organization B is an economic development and organization C is a research and development organization. The study was conducted by means of qualitative research methodology. This means that the focus was to understand an event and its interaction within the natural context in order to determine what and how to build a learning organization. The study found that the building of learning organization are varies and indicates some evolving elements. It was observed that the elements of supporting the building of a learning organization were interpreted based on the organization’s own identity. As a conclusion, it can be said that the study had shed some light on suggesting the elements of supporting the building of a learning organization. It also contributes to the upgrading and promoting the understanding and to enable the organizations concerned to develop into full-pledge learning organization